Overview Of Environmental Conditions That Have The Potential To Become A Breeding Place For Mosquitoes That Cause Dengue Hemorrhagic Fever (Dhf) In Cikulak Village, Cirebon Regency - Gita Bestari; Cucun Novita; Clarissa Maharani Aprillia; Doni Kurniadi Putra; Amanda Elvina (CV. AFDIFAL MAJU BERKAH, 2026)
Mosquitoes are a vector of disease that plays a role in the spread of various infectious diseases, such as dengue fever (DHF), malaria, chikungunya, and filariasis. Environmental conditions such as stagnant water, open water reservoirs, and garbage accumulation can serve as breeding grounds for mosquitoes and increase the risk of disease transmission. This study aims to identify environmental conditions that have the potential to become mosquito breeding grounds in Cikulak Village, Cirebon Regency. The study used a descriptive observational design with a cross-sectional approach and was conducted in Cikulak Village, Cirebon Regency, from February to March 2026. The results revealed the presence of rarely cleaned bathtubs containing mosquito larvae, used containers that collect rainwater, stagnant water around houses, and garbage accumulation in residential areas. These conditions have the potential to become mosquito breeding grounds. Therefore, the environmental conditions in Cikulak Village still have the potential to become mosquito breeding grounds, requiring environmental management efforts and increased public awareness to prevent mosquito breeding.